Comprehensive Analysis of Metabolic Changes in Male Mice Exposed to Sodium Valproate Based on GC-MS Analysis - Gao Y; Jiang D; Wang C; An G; Zhu L; Cui C (Dove Medical Press, 2022)
Yahao Gao,1,* Di Jiang,2,* Changshui Wang,3 Gang An,1 Li Zhu,4 Changmeng Cui3 1Clinical Medical School, Jining Medical University, Jining, Shandong, People's Republic of China; 2Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of China; 3Department of Neurosurgery, Affiliated Hospital of Jining Medical University, Jining, People's Republic of China; 4Department of Clinical Pharmacy, Jining First People's Hospital, Jining Medical University, Jining, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Changmeng Cui, Department of Neurosurgery, Affiliated Hospital of Jining Medical University, 89 Guhuai Road, Jining, Shandong, 272000, People's Republic of China, Tel +8617805378911, Email cmcuidr1989@163.comPurpose: Sodium valproate (VPA) is the most widely used broad-spectrum antiepileptic first-line drug in clinical practice and is effective against various types of epilepsy. However, VPA can induce severe cardiotoxicity, nephrotoxicity, hepatotoxicity, and neurotoxicity, which limits its use. Metabolomic studies of VPA-induced toxicity have focused primarily on changes in serum and urine metabolites but have not evaluated changes in major organs or tissues.Methods: Central target tissues (intestine, lung, liver, hippocampus, cerebral cortex, inner ear, spleen, kidney, heart, and serum) were analyzed using gas chromatography mass spectrometry to comprehensively evaluate VPA toxicity in mouse models.Results: Multivariate analyses, including orthogonal projections of the latent structure and Student's t test, indicated that depending on the matrix used in the study (the intestine, lung, liver, hippocampus, cerebral cortex, inner ear, spleen, kidney, heart or serum) the number of metabolites differed, the lung being the poorest and the kidney the richest in number.Conclusion: These metabolites were closely related and were found to participate in 12 key pathways related to amino acid, fatty acid, and energy metabolism, revealing that the toxic mechanism of VPA may involve oxidative stress, inflammation, amino acid metabolism, lipid metabolism, and energy disorder.Keywords: sodium valproate, biomarker, gas chromatography mass spectrometry, metabolomics, toxicity mechanism